2022
DOI: 10.3390/ijerph20010625
|View full text |Cite
|
Sign up to set email alerts
|

Does Quality of Care (QoC) Perception Influence the Quality of Life (QoL) in Women with Endometriosis? Results from an Italian Nationwide Survey during Covid Pandemic

Abstract: (1) Background: Endometriosis is a chronic and progressive illness that generates a slew of issues, lowering the quality of life of women. The purpose of this study was to look at the quality of life in women with endometriosis and how it relates to the quality of care. (2) Methods: This study is an online survey performed in Italy during the COVID pandemic using the Italian version of the Health Questionnaire SF-36 and a questionnaire for assessing the quality of care received. (3) Results: 1052 women with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The present study represents a secondary analysis of a data set from the project “Quality of care and perception of quality of life in women with endometriosis in the covid era”, the results of which have already been partially reported [ 17 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study represents a secondary analysis of a data set from the project “Quality of care and perception of quality of life in women with endometriosis in the covid era”, the results of which have already been partially reported [ 17 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The illness has a substantial impact on women’s social activities, sexual relationships, and mental and emotional health [ 14 , 15 , 16 ]. Scientific research has shown that endometriosis can lower physical QoL to a level comparable to the physical QoL perceived by cancer patients [ 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This project aimed to investigate the QoL in women with endometriosis and the eventual impact on it or the QoC. 6 The STROBE Guidelines were used to ensure the reporting of this observational study.…”
Section: Methodsmentioning
confidence: 99%
“…Endometriosis has been linked to decreased psychological and social well-being and has a detrimental effect on all aspects of QoL. 4 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation